(untitled) (El Hilo de la Fabula, 2021)
As it is well known, the transformations of the nineteenth-century realistic narrative and the questioning of this aesthetic by twentieth-century authors and critics have called into question the idea of ​​writing as a mimetic representation of reality. In detracting from the plausible realist, not only the historical avant-garde played a relevant role, but also many of the narrative forms grouped, in the absence of a more precise name, under the term «non-fiction» (documentary novels, biographies, autobiographies, testimonies, among others). It is in this line that the writing of the Argentine Rodolfo Walsh, author of research works that embody not so much a will to represent the real as to produce an intervention in the real by denouncing silenced State crimes. In Walsh’s books, the non-fiction work is evidenced by the selection, montage and narrativization operated on the testimonial material (Amar Sánchez). This form of Walshian intervention can be put into dialogue with some of the features present in the chroniclers of the Southern Cone, situated at the dawn of the twenty-first century: the critical look towards society and the journalist’s adoption of a voice of its own; the interest in the marginal subjects of the system; the display of an experimental attitude in writing; the search for an audience; the postulate of journalistic exercise as a political intervention. This paper aims to examine two biographical works of Latin American female chroniclers in parallel: Opus Gelber. Retrato de un pianista (2019), by Leila Guerriero, and La hermana menor (2018), by Mariana Enriquez. The purpose of the dialogue between the two profiles is to contribute to the delimitation of the forms of intervention on reality by current authors of narrative journalism.